2012
DOI: 10.5194/acp-12-7399-2012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two isoprene emission models for use in a long-range air pollution model

Abstract: Abstract. Knowledge about isoprene emissions and concentration distribution is important for chemistry transport models (CTMs), because isoprene acts as a precursor for tropospheric ozone and subsequently affects the atmospheric concentrations of many other atmospheric compounds. Isoprene has a short lifetime, and hence it is very difficult to evaluate its emission estimates against measurements. For this reason, we coupled two isoprene emission models with the Danish Eulerian Hemispheric Model (DEHM), and eva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…Zare et al (2012) simulated isoprene overestimation for 4 European sites (between a factor 2 and 10), good agreement (within +/-30%) for 2 sites and an underestimation for 2 sites (also between a factor 2 and 10). However, none of the sites was located close to the Mediterranean Sea.…”
Section: Gaseous Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zare et al (2012) simulated isoprene overestimation for 4 European sites (between a factor 2 and 10), good agreement (within +/-30%) for 2 sites and an underestimation for 2 sites (also between a factor 2 and 10). However, none of the sites was located close to the Mediterranean Sea.…”
Section: Gaseous Speciesmentioning
confidence: 99%
“…The local character of the comparisons for biogenic VOCs was pointed out, as well as the fact that biogenic OA is formed at a regional scale from these precursors rather than a 10 local scale. Available regional comparisons show acceptable comparisons for BVOC observed and simulated concentrations (Curci et al, 2010 ;Zare et al, 2012 ;Fares et al, 2013).Therefore, a systematic misrepresentation of BVOC in the model seem to be unlikely. For aerosol species, low bias was seen for BC, while an overestimation in simulations is observed for sulfates.…”
Section: Particulate Speciesmentioning
confidence: 99%
“…Jansen and De Serves, 1998;Lindfors and Laurila, 2000). Recently comparisons of European isoprene mixing ratios calculated online in a CTM with MEGAN against similar EMEP data for 2006 have also shown that there is a wide variability in agreement between different EMEP sites even when including yearly specific meteorological variability during the derivation of emission fluxes (Zare et al, 2012). Figure 8 shows the seasonal cycle in tropospheric CO as observed at 12 measurement sites in the GMD network, with the location of each measurement site being given in the figure caption.…”
Section: Isoprenementioning
confidence: 99%
“…global isoprene and terpene emissions have already received some attention in the literature (e.g. Arneth et al, 2008;Williams et al, 2009;Zare et al, 2012). Figure 2a-d shows the seasonal climatological cycles for CO, C 2 H 4 , C 2 H 6 and CH 3 COCH 3 for each of the four chosen BVOC inventories (solid lines) both globally and for each of the five pre-defined regions.…”
Section: Comparison Of Biogenic Emission Inventoriesmentioning
confidence: 99%
“…GEOS-Chem and other chemical transport models have previously shown a large sensitivity to land cover data sets (Li et al, 2013) and biogenic emission models (Fiore, 2005;Kim et al, 2014;Zare et al, 2012). Globally, we find annual emissions of isoprene decrease by 14 % from 531 to 459 Tg yr −1 with land use harmonization and updated emission factors.…”
Section: Impact Of Updates and Land Use Harmonization On Geos-chem Simentioning
confidence: 58%